(untitled) (Research, Society and Development, 2022)
For decades, studies have analyzed the use of bleach, which has sodium hypochlorite in its composition, in endodontic treatment. Sodium hypochlorite (NaOCl) is considered the most widely used irrigating solution in endodontic therapy worldwide. The predilection for this substance is attributed to the fact that it has two extremely important properties: antimicrobial action and tissue dissolution capacity. However, NaOCl has some disadvantages that must be taken into account before its use, such as its cytotoxic potential, which is irritating to periradicular tissues. Based on this information, the present study aimed to evaluate the use of bleach in endodontic treatment. We sought to report the various concepts in relation to their use in an effective and safe way during endodontic therapy. In the methodology, a documental study was carried out based on the periodical databases Google Scholar and Scielo, whose time frame comprised the period between the years 1999 to 2021. The results showed that Endodontics has been modernizing, especially its instrumentation techniques, such as the use of bleach. In this case, the use of bleach effectively promotes sanitation and decontamination of the complex root canal system.